2014
DOI: 10.1007/s12665-014-3787-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the hypothetical methane-leakage in a shale-gas project and the impact on groundwater quality

Abstract: The hypothetical leakage of methane gas caused by fracking a 1,000-m deep Cretaceous claystone horizon at Damme, Germany, is simulated in a TOUGH-REACT reactive-transport model with 5,728 elements. A hypothetical leakage zone connects the Cretaceous horizon with a Quaternary potable-water aquifer (q1). Methane gas rises up to the q1 horizon in less than 2 days in all calculated scenarios. The simulations include the major constituents of groundwater as well as the seven most hazardous trace components that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…van Breukelen and Griffioen (2004) and van Breukelen et al (2004) observed and modeled an increase in pH and calcite precipitation during anaerobic degradation of methane at the fringe of a landfill plume. Although only a modeling exercise, Schwartz (2015) reported similar results during anaerobic methane oxidation with an increase in pH as well as a drop in most trace element concentrations, consistent with the assumed conceptual model that sorption controls their concentrations.…”
Section: Discussionsupporting
confidence: 67%
“…van Breukelen and Griffioen (2004) and van Breukelen et al (2004) observed and modeled an increase in pH and calcite precipitation during anaerobic degradation of methane at the fringe of a landfill plume. Although only a modeling exercise, Schwartz (2015) reported similar results during anaerobic methane oxidation with an increase in pH as well as a drop in most trace element concentrations, consistent with the assumed conceptual model that sorption controls their concentrations.…”
Section: Discussionsupporting
confidence: 67%
“…Model calculations on methane migration often result in a release to the atmosphere (e.g. Sauter et al 2012;Schwartz 2015). As long as it can migrate as a free phase, methane is driven upward due to its significantly lower density and therefore is more likely to reach surficial aquifers (if continuously permeable structures exist).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most studies published so far, fluid flow is simulated not only in highpermeability zones (e.g. Myers 2012;Sauter et al 2012;Chesnaux et al 2013;Schwartz 2015) but also in open fractures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations